Technologies for Obtaining Modified Sulfur Concrete Based on Local Raw Materials - Pulatova Kh. Kh; Beknazarov Kh.S; Khayitova Zh M.; Sayfulla I. N. (Genius Journals, 2023)
In this article, the technology of obtaining modified sulfur and obtaining sulphurconcrete from the obtained product is studied.A variety of organic compounds have been used as elemental sulfur modifying additives, and almost all of them have been studied as polymeric polysulfides or, alternatively, olefinic hydrocarbons. As a result, sulfur can be used as an additive in construction materials such as concrete and asphalt. In this case, it was determined that the highest productivity and the degree of polymerization are higher than those obtained in a 1:1 mol ratio of the initial substances in the production of sulfur modification. Also, the effect of temperature on the modification was studied. The obtained results revealed their structure using IR spectra. Based on the research results, it was described that the obtained modified sulfur concrete gives strength and durability to sulfur concrete even in high concentrations of acids or salts with the help of unsaturated organic binders.
Keywords: modified sulfuric; sulphur; polymer modified sulfur; expanded clay